Proposals of environmental education to irregular disposal of construction solid wastes in campinas, SP State, Brazil - Kawatoko, Ivie Emi Sakuma; Silva, Caio Henrique Martins (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Currently, more than 100.000 t/day of construction waste are generated in Brazil, besides Campinas-SP contributes with a value about 3.000 t/day.According toPolicy of Solid Wastes (Federal Law nº 12.305/2010), as well as CONAMA Resolutions nº 307/2002 andnº 448/2012, this class of solid wastes demands the elaboration of “Municipal Management Plans of Construction Wastes”. Thepresent work aims to collaborateto environmental planningwith a diagnosis of irregular disposal of construction solid wastes in Campinas and proposals of environmental education measures.In this way, sampling fields were applied –adopting the Administrative Regions (AR) as planning units –to identify and map the most critical points of irregular disposal in city. All inspections were accompanied by an environmental supervisor.As a result, a total of twentyfour critic points were inspected and mapped, all them distributed on peripheral areas. Thus, it was proposed some environmental education measures, grouped on three hubs: large generators; small generators and sustainability in construction.